2021
DOI: 10.1186/s12884-021-03542-w
|View full text |Cite
|
Sign up to set email alerts
|

‘The newest vital sign among pregnant women attending women wellness and research Centre in Qatar: a cross-sectional study’

Abstract: Background Health literacy is a vital strategy to consider when designing health-promoting programs, and health literacy is a priority in Qatar’s national health agenda. In the context of pregnancy, inadequate health literacy has been linked to several adverse outcomes among pregnant women such as unplanned conception, smoking, and lack of multi-vitamin intake. Given the paucity of data, this study aimed to assess the level of health literacy and its determinants among pregnant women in the Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…Findings from this study are in agreement with studies conducted in Qatar, 29 Iran, 30 and Turkey 31 that found that lower levels of education, low income, and unemployment were associated with low health literacy levels among pregnant women. 29 31 Likewise, health literacy was significantly associated with factors such as employment status and level of education among female primary care patients in Korea and Serbia. 32 , 33 A current study indicated that women who have adequate literacy levels tend to worry less about the birth.…”
Section: Discussionsupporting
confidence: 91%
“…Findings from this study are in agreement with studies conducted in Qatar, 29 Iran, 30 and Turkey 31 that found that lower levels of education, low income, and unemployment were associated with low health literacy levels among pregnant women. 29 31 Likewise, health literacy was significantly associated with factors such as employment status and level of education among female primary care patients in Korea and Serbia. 32 , 33 A current study indicated that women who have adequate literacy levels tend to worry less about the birth.…”
Section: Discussionsupporting
confidence: 91%
“… 25 It was shown to be a reliable and valid HL measure, validated against standard HL assessments such as the Test of Functional Health Literacy in Adults. 25 , 26 The NVS has been studied in several countries in general community samples 26–29 and in pregnant women, 30 and thus supports internationally comparable HL research. Literature searches conducted before the study did not identify any Vietnamese-language versions of the NVS that had been used or validated for HL screening in Vietnamese populations.…”
Section: Methodssupporting
confidence: 61%
“…The NVS is a brief HL screening instrument used to assess functional HL (38). Originally developed in English and Spanish, and validated in the United States, the NVS has been adapted and validated for use in other languages and countries in general population settings (39)(40)(41)(42), and in various groups, including caregivers of children (43) and pregnant women (44). As a brief instrument, the NVS was considered suitable for this research program due to its ease of use and acceptability to research subjects.…”
Section: Newest Vital Signmentioning
confidence: 99%